ANALISIS TINGKAT DEPRESI PADA LANSIA BERDASARKAN STATUS SOSIAL EKONOMI - Utami, Utami; Sulistiyani, Sulistiyani; Suyanti, Titi Sri (Ensiklopedia of Journal, 2025)
Abstract: Depression is a serious mental health disorder with a high prevalence worldwide. The incidence of depression in the elderly both living in nursing homes and in the community tends to increase with age. The purpose of the study was to analyze the level of depression in the elderly based on socioeconomic status. The research design used in this study was cross sectional. The research was conducted in the working area of the Danau Indah Health Center. The research was conducted in August 2024. The population is all elderly people who live in the Danau Indah Health Center working area. The sample amounted to 176 respondents. The sampling technique used in this study was Consecutive Sampling. Data analysis was carried out univariate and bivariate. The results showed a relationship between age (p value: 0.000) and Economic Status (p value: 0.000) on the risk of depression in the elderly. It is recommended for elderly family members to encourage elderly family members to remain socially active, both through interactions with family, neighbors, and the elderly community.Keywords: Depression, Elderly, Economic Status.